Respostas
respondido por:
1
10 / 3x = 15 / 4x + 1
15 . 3x - 10(4x + 1)
45x = 40x + 10
45x - 40x = 10
5x = 10
x = 10 / 5
x = 2
15 . 3x - 10(4x + 1)
45x = 40x + 10
45x - 40x = 10
5x = 10
x = 10 / 5
x = 2
respondido por:
1
A resolução é o seguinte :
15/3x = 10/4x+1
3x.(10) = 15.(4x+1)
30x = 60x +15
30x -60x = 15
-30x = 15
x = 15/-30
x = -0,5
Tirando à limpo :
15/ 3. (-0,5) = 10/4.(-0,5) + 1 →
→ 15/-1,5 = 10/-2 +1
→15/-1,5 = 10/-1
→ -10 = -10
As bases foram igualadas. Encerramos a operação.
Espero ter ajudado ;)
15/3x = 10/4x+1
3x.(10) = 15.(4x+1)
30x = 60x +15
30x -60x = 15
-30x = 15
x = 15/-30
x = -0,5
Tirando à limpo :
15/ 3. (-0,5) = 10/4.(-0,5) + 1 →
→ 15/-1,5 = 10/-2 +1
→15/-1,5 = 10/-1
→ -10 = -10
As bases foram igualadas. Encerramos a operação.
Espero ter ajudado ;)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás